"They tell you that in school you'll be better off, but it's the same old thing”. The educational system between necropolitics and transformative pedagogies (Praxis Educativa, 2021)
This work is grounded in my professional practice as a teacher in middle schools in vulnerable neighborhoods in the southern part of the city of Buenos Aires. In this article I will focus on the relationship between middleschool education for teenagers from vulnerable contexts and specific processes of violence and exclusion such as "slow death" and "necropolitics". The hypothesis I will present is that in certain contexts, the educational system encourages and (re)produces a politics of death that exposes these male identities to greater risk. I will also contend that this has its correlation in the construction of identities. Finally, I will suggest that critical and queer pedagogies can provide tools for resistance and transformation.
Keywords: necropolitics; slow death; teenagers; queer pedagogy; educational system